Obstetrics and gynaecology - Cruickshank, Maggie; Shetty, Ashalatha (Clinical cases uncovered, 2009)
Featuring a range of commonly encountered and important conditions in women's health, Obstetrics & Gynaecology: Clinical Cases Uncovered allows the reader to understand normal reproductive physiology and anatomy in the context of clinical practice.